Clinical Protocol for a Longitudinal Cohort Study Employing Systems Biology to Identify Markers of Vaccine Immunogenicity in Newborn Infants in The Gambia and Papua New Guinea - Idoko, Olubukola T.; Smolen, Kinga K.; Wariri, Oghenebrume; Imam, Abdulazeez; Shannon, Casey P.; Dibassey, Tida; Diray-Arce, Joann; Darboe, Alansana; Strandmark, Julia; Ben-Othman, Rym; Odumade, Oludare A.; McEnaney, Kerry; et al. (Frontiers in Pediatrics, 2020)
Background: Infection contributes to significant morbidity and mortality particularly in the very young and in low- and middle-income countries. While vaccines are a highly cost-effective tool against infectious disease little is known regarding the cellular and molecular pathways by which vaccines induce protection at an early age. Immunity is distinct in early life and greater precision is required in our understanding of mechanisms of early life protection to inform development of new paediatric vaccines. Methods and analysis: We will apply transcriptomic, proteomic, metabolomic, multiplex cytokine/chemokine, adenosine deaminase and flow cytometry immune cell phenotyping to delineate early cellular and molecular signatures that correspond to vaccine immunogenicity. This approach will be applied to a neonatal cohort in The Gambia (N ~720) receiving at birth: 1) Hepatitis B (HepB) vaccine alone, 2) Bacille Calmette Guerin (BCG) vaccine alone, or 3) HepB and BCG vaccines, 4) HepB and BCG vaccines delayed till day 10 at the latest. Each study participant will have a baseline peripheral blood sample drawn at DOL0 and a second blood sample at DOL1, -3, or -7 as well as late timepoints to assess HepB vaccine immunogenicity. Blood will be fractionated via a “small sample big data” standard operating procedure that enables multiple downstream systems biology assays. We will apply both univariate and multivariate frameworks and multi-OMIC data integration to identify features associated with anti-Hepatitis B (anti-HB) titre, an established correlate of protection. Cord blood sample collection from a subset of participants will enable human in vitro modelling to test mechanistic hypotheses identified in silico regarding vaccine action. Maternal anti-HB titre and the infant microbiome will also be corelated with our findings which will be validated in a smaller cohort in Papua New Guinea (N ~80). Ethics and Dissemination: The study has been approved by The Gambia Government/MRCG Joint Ethics Committee and The Boston Children’s Hospital Institutional Review Board. Ethics review is ongoing with the Papua New Guinea Medical Research Advisory Committee. All de-identified data will be uploaded to public repositories following submission of study output for publication. Feedback meetings will be organised to disseminate output to the study communities.